Giant Cell Fibroma of Tongue: Understanding the Nature of an Unusual Histopathological Entity - Wanjari Ghate Sonalika; Anshuta Sahu; Suryakant C. Deogade; Pushkar Gupta; Dinesh Naitam; Harsh Chansoria; Jatin Agarwal; Shiva Katoch (Hindawi Limited, 2014)
Giant cell fibroma (GCF) is a rare case with unique histopathology. It belongs to the broad category of fibrous hyperplastic lesions of the oral cavity. It is often mistaken with fibroma and papilloma due to its clinical resemblance. Only its peculiar histopathological features help us to distinguish it from them. The origin of the giant cell is still controversial. Data available is very sparse to predict the exact behavior. Hence, we report a case of GCF of tongue in a 19-year-old male. Special emphasis is given to understand the basic process of development of the lesion, nature of giant cells, and also the need for formation of these peculiar cells. Briefly, the differential diagnosis for GCF is tabulated.